Notaris sebagai Penerima Tanggung Jawab atas Draft Akta yang Dihasilkan oleh Kecerdasan Buatan (AI) - Riyanti, Meita Debi (Fakultas Hukum Universitas Airlangga, 2025)
The rapid development of Artificial Intelligence (AI) has introduced significant innovations in the legal field, including notarial practice. One of its applications is the automatic drafting of contracts or deeds through AI systems. While this technology offers efficiency and accuracy, it simultaneously raises new legal issues, particularly concerning the notary’s liability as a public official authorized to draw up authentic deeds. The objective of this study is to analyze the legal status of AI-generated drafts within notarial practice and to examine the extent of notarial responsibility for deeds prepared based on such drafts. This research applies a normative juridical method, employing statutory, doctrinal, and legal principle approaches. Primary legal sources consist of the Indonesian Notary Law (UU Jabatan Notaris/UUJN), while secondary materials are drawn from scholarly works on notarial law and legal technology studies. The findings indicate that AI, as a mere tool, does not possess legal authority to create deeds, and therefore cannot diminish the notary’s responsibility. The notary remains fully accountable for the validity, substance, and evidentiary strength of authentic deeds, regardless of whether the draft originates from AI. This conclusion aligns with the principles of personal liability, the duty of prudence, and professional responsibility inherent in the notarial office. Consequently, adaptive regulation—either through amendments to the Notary Law or professional guidelines—is urgently required to ensure legal certainty while accommodating technological advancement.